THE DEVELOPMENT OF BASIC MATHEMATICS TEXTBOOK TO ENHANCE STUDENT LEARNING OUTCOMES IN THE FACULTY OF EDUCATION AT PUTRA INDONESIA YPTK UNIVERSITY PADANG - Lili Rismaini; Dewi Devita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
The presence of textbooks as a learning medium and/or source for students in their coursework essentially aims to facilitate their learning. Lecturers develop a Basic Mathematics textbook designed systematically to aid students in their learning and enhance their learning outcomes. The research subjects are 25 students from the Technical Informatics Education program taking the Basic Mathematics course. The objective of this research is to develop a textbook that aligns with the needs of the coursework and assess its practicality. The research method used is research and development, using the ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation). During the implementation phase, practicality testing is conducted to determine how practical the Basic Mathematics textbook is for student learning. The research findings indicate that the Basic Mathematics textbook exhibits a high level of practicality, suggesting its suitability for improving students' mathematics learning outcomes. The research results also show that in the effectiveness phase, statistical analysis using the Paired Sample Test yielded a two-tailed significance value of 0.000, which is less than the alpha value of 0.05. This implies that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Hi) is accepted, indicating a significant difference in students' mathematics learning outcomes before and after using the Basic Mathematics textbook.